The Influence of Principal Leadership and Organizational Culture on School Excellence in Vocational Schools in Ende City: Case Study at SMK Negeri 1 Ende - Maria Meilania Belo Silli; Imaculata Fatimah; Mansyur Abdul Hamid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine and analyze the magnitude of the influence of the principal's leadership on the excellence of the State Vocational High School 1 Ende. In addition, to determine and analyze the magnitude of the influence of organizational culture on the excellence of the State Vocational High School 1 Ende. As well as, to know and analyze the magnitude of the influence of the principal's leadership and school organizational culture on the excellence of the State Vocational High School 1 Ende. This study used a quantitative approach with a survey research design. Data were collected through questionnaires distributed to teachers and employees at SMK Negeri 1 Ende. Furthermore, the data were processed using SPSS software version 25 for windows 2010 including descriptive, correlative, and simple regression analysis. Based on the analysis, it is known that school excellence at SMK Negeri 1 Ende is good. This is indicated by the accreditation score owned by SMK Negeri 1 Ende. Through simple regression analysis, it is found that the principal leadership variable (X1) and organizational culture (X2) have an effect of 50.2% on school excellence, and the coefficient of determination is 0.502. Based on the results of the study, it is concluded that school excellence is influenced, among others, by the leadership of the principal, school organizational culture. However, outside of these two variables, there are still many other factors that influence. For this reason, it is recommended that the principal of Smk Negeri 1 Ende improve human resources by continuing studies for teachers, trainings, leadership training, motivating students and teachers who excel, revitalizing cultural values as well as filtering potential children's input.